RETRACTED: New Schemes for Investment in of Small and Medium-Sized Enterprises of China: Role of Access to Finance, Innovation, and Sustainability - Tang, Xuelian (Frontiers in Psychology, 2022)
To better understand the nature of the impact of financial literacy, innovation, and corporate social responsibility on the adoption of sustainable business models practices. The study investigates how financial literacy, innovativeness, and environmental sustainability influence small and medium (SMEs) firms’ sustainability. We develop a conceptual model that identifies the factors that influence sustainable business practices in China. In order to test the hypotheses, structural equation modeling (SEM) is applied using data collected from 350 small businesses firms in China. The results reveal that financial literacy and innovativeness significantly influence small firms’ sustainability, respectively. Additionally, social responsibility significantly affects small firms’ sustainability, and sequentially has a significant effect on performance. The most notable of these is that access to finance is a mediating function in the relationships between financial literacy and innovativeness. To maintain sustainability, the study suggests that small businesses incorporate sustainability models into their operations and improve their financial knowledge.